APCDs can Provide Important Insights for Surveilling the Opioid Epidemic, With Caveats. (August 2022) - Buttorff, Christine; Wang, George S.; Tung, Gregory J.; Wilks, Asa; Schwam, Daniel; Pacula, Rosalie Liccardo
State-level all-payer claims databases (APCDs) are a possible new public health surveillance tool, but their reliability is unclear. We compared Colorado's APCD with other state-level databases for use in monitoring the opioid epidemic (Colorado Hospital Association and Colorado's Prescription Drug Monitoring Program database for 2010–2017), using descriptive analyses comparing quarterly counts/rates of opioid-involved inpatient and emergency department visits and counts/rates of 30-day opioid fills between databases. Utilization is lower in the Colorado APCD than the other databases for all outcomes but trends are parallel and consistent between databases. State APCDs hold promise for researchers, but they may be better suited to individual-level analyses or comparisons of providers than for surveillance of public health trends related to addiction.